Hubungan Kejadian Kondiloma Akuminata Terhadap Kualitas Hidup Pekerja Seks Komersial di Hotspot Pekanbaru - Puteri Maharani; Rina Amtarina; Alida Widiawaty (Jurnal Ilmu Kedokteran, 2018)
Genital Warts (GW) is one of the most common clinical manifestations of human papillomavirus (HPV) infection. GW patients experience discomfort and anxiety about the effects of illness that will affect their quality of life (QOL). The purpose of this study was to analyze the relationship between GW and QOL of Female Sex-Workers (FSW) in hotspot X of Pekanbaru which involved 49 FSW by using total sampling technique. The QOL data was taken by using WHOQOL-BREF questionnaire that consists of physical, psychological, social, and enviromental score. whereas the GW data from physical examination. Data were analyzed by using t-test and Mann Whitney. The t-test showed the result of psychological score (p=0,000), environmental score (p=0,463). The Mann-Whitney test showed the result physical score (p=0,007), social score (p=0,019). It could be concluded that there was a relationship between GW with physical, psychological, and social scores, but no relationship with environmental score.